Litiasis ureteral - Montenegro, Antonio (1937)
A statistical review of the patients with ureteral lithiasis, interned in the Urological Clinic, in the teaching services of the authors, from 1925 to june 1934, is presented. The authors indicate, as an absolute necessity to make a complete Radiographic examination of the urinary apparatus, of all sus pected cases of Renal calculus. They establish that the therapeutic procedure to be follewed, according to the distinct cases which present themselves.